Viscosities of Binary Liquid Mixtures of Acetylene Tetrachloride with Benzene, Toluene, p-xylene, Acetone & Cyclohexane at 303.15K - Tripathi, Atri Deo; Agrawal, Meenu (Journal of Applied Solution Chemistry and Modeling, 2014)
Viscosities which are accurate to ± 0.01mP, have been measured for binary liquid mixtures of acetylene tetrachloride (CHCl2CHCl2, hereafter abbreviated simply as ATC) with benzene, toluene, p-xylene, acetone and cyclohexane at 303.15 ±0.01K. The values of the quantity Δη, which refer to the deviations of the experimental values of the dynamic viscosities of the mixtures from the mole fraction mixture law values, have been found to be negative for the systems ATC-benzene, ATC-toluene, ATC-p-xylene and ATC-cyclohexane. For ATC-acetone, Δη has been found to be negative at low mole fractions of ATC and positive at high mole fractions. Also the values of the parameter d have been calculated from the equation ln η = x1 ln η1+x2 ln η2 +x1 x2 d, where η1 & η2 refer to the dynamic viscosities of the two pure liquids 1 and 2 whose mole fractions in the mixtures are x1 & x2 respectively. The values of d indicate the existence of specific interaction of ATC with benzene, toluene, p-xylene and acetone. The viscosity data have been analysed in the light of absolute reaction rate and free volume theories of liquid viscosity.